Potential Immunogenic Polypeptides of Burkholderia pseudomallei Identified by Shotgun Expression Library and Evaluation of Their Efficacy for Serodiagnosis of Melioidosis - Puah, Suat Moi (Ivyspring International Publisher, 2013)
The search for novel immunogenic polypeptides to improve the accuracy and reliability of serologic diagnostic methods for Burkholderia pseudomallei infection is ongoing. We employed a rapid and efficient approach to identify such polypeptides with sera from melioidosis patients using a small insert genomic expression library created from clinically confirmed local virulent isolates of B. pseudomallei. After 2 rounds of immunoscreening, 6 sero-positive clones expressing immunogenic peptides were sequenced and their identities were: benzoate 1,2-dioxygenase beta subunit, a putative 200 kDa antigen p200, phosphotransferase enzyme family protein, short chain dehydrogenase and 2 hypothetical proteins. These immunogens were then transferred to an ELISA platform for further large scale screening. By combining shotgun expression library and ELISA assays, we identified 2 polypeptides BPSS1904 (benzoate 1,2-dioxygenase beta subunit) and BPSL3130 (hypothetical protein), which had sensitivities of 78.9% and 79.4% and specificities of 88.1% and 94.8%, respectively in ELISA test, thus suggesting that both are potential candidate antigens for the serodiagnosis of infections caused by B. pseudomallei.